Neuropeptides in the human brainstem - Duque-Díaz, Ewing; Martínez-Rangel, Diana; Ruiz-Roa, Silvia (Investigación Clínica, 2018)
The physiological importance of the brainstem has made it one of the most studied structures of the central nervous system of mammals (in- cluding human). This structure receives somatic and visceral inputs and its neurons send motor efferences by means of the cranial nerves, which innervate the head, neck and sensory organs, and it mediates in several actions such as movement, pain, cardiovascular, respiratory, salivary, sleep, vigil and sexual mechanisms. Most of these actions are mediated by neuroactive substances denominated neuropeptides, which are short amino acid chains widespread dis- tributed in the nervous system, that play a role in neurotransmission, neuro- modulation (paracrine and autocrine actions), and act as neurohormones. In- creased study of these substances has taken place since the 1980s to shed light on both their potential role and the way that they mediate in the organism’s different activities. Thus, our aim is a detailed review of available morphologic and physiologic data regarding some neuropeptides in the human brainstem. To such end, we will discuss aspects like: 1) the distribution of neuropeptides in the human brainstem; 2) their possible physiological actions in the human brainstem; 3) neuropeptide coexistences in the human brainstem; and 4) fu- ture research in neuropeptides in the human brainstem.